Disaster Mitigation Innovation: Lessons Learned at a Regional Disaster Management Agency in South Sulawesi - Halim, Halim; Asmarianti, Asmarianti; Basri, Muhammad (KnE Social Sciences, 2022)
Natural disasters are becoming more common in Indonesia, and their severity is increasing. To meet the challenges of updating disaster mitigation and rehabilitation capabilities, more innovative or better technology is required. In an effort to mitigate and overcome disasters, an innovation known as Simpul Pena has been developed. Simpul Pena is an information system for the control and operational center for disaster management in the regional disaster management agency (BPBD) in Wajo Regency. This study applied a qualitative descriptive approach. Data were collected through interviews, observations and document review. Interviews were conducted with the Head of BPBD Wajo Regency and the Head of the Emergency and Logistics Division, while observations were carried out to gain an understanding of the process of implementing public service innovations at the BPBD Wajo Regency. The results of the study showed that the implementation of the Simpul Pena innovation was effective and there has been consistency in its application. The impact of Simpul Pena was measured using five factors that can contribute to the success of innovation: leadership, management/organization, risk management, human resources, and technology. Disaster information system services were carried out through Simpul Pena via access to WhatsApp, Facebook and Instagram, resulting in integrated, coordinated, efficient and effective disaster management, as well as a significant increase in community participation in disaster management. The role of leadership was the most influential factor in shaping an innovative culture and behavior so that the organization continued to improve in developing service innovations to meet the challenges faced. Keywords: public sector innovation, disaster mitigation, regional disaster management agency, Wajo Regency, South Sulawesi Province